STRATEGI PENGELOLAAN HUTAN KOTA WADUK SUNTER UTARA DALAM RANGKA MEMPERTAHANKAN FUNGSI WADUK SEBAGAI RESAPAN AIR - Sri Rahayu Maykewati (Program Studi Manajemen Lingkungan, 2017)
Forest of North Sunter Reservoir is one of the urban forest that has been determined by Decree of Jakarta Governor No.317 Year 1999 about Sunter North Road Forest Size Establishment +2,2 ha as jungle city forest in North Jakarta Municipality. This study aims to find out how the strategy of Forest Management of North Sunter Reservoir City that can be applied, how the role of stakeholders in management, internal and external factors what, what solution has been done and how the success and what the future expectation. The method used is descriptive qualitative approach. Data collection techniques and procedures used are: (1) Observation; (2) Interviews; (3) Documents; (4) FGD (Focus Group Discussion). The analysis was conducted using environmental analysis, stakeholder analysis, SWOT analysis (Strength Weakness Opportunity Treath) and QSPM (Quantitative Strategic Planning Matrix) analysis.The North Sunter City Forest Management Strategy can be implemented with the collaboration of relevant stakeholders, it is expected to increase the benefit value of its strengths and opportunities, and can minimize the value of weaknesses and threats, so that the North Sunter Reservoir Forest can function optimally and can maintain the function of the reservoir water infiltration.